Strongly (V?, ?, q)-summable sequences a defined by Orlicz functions - Güngör, M; Et, M; Altin, Y (Elsevier Science Inc, 2004)
The purpose of this paper is to introduce the space of sequences that are strongly (V-sigma,lambda,q)-summable with respect to an Orlicz function. We give some relations related to these sequence spaces. We also show that the spaces [ Vsigma,lambda,M,p,q](1) boolean AND l(infinity)(q) may be represented as a S* boolean AND l(infinity)(q) space. (C) 2003 Elsevier Inc. All rights reserved.
Keywords: sequence spaces; seminorm; statistical convergence; Orlicz function